Exploring Different Motivational Factors Between Employees and Senior Managers - Choo, Stephanie Huae Sien (2010)
Motivation fuels passion and pushes one to achieve his ultimate potential allowing him to achieve greater heights. It drives the ordinary performer into becoming an extraordinary one. Appropriate motivation is like oxygen for humans; it is important. Not only does it provide the passion and get the blood going, it ultimately serves as the engine for an individual’s survival in this cut throat, competitive world. Having developed an immense passion on the subject matter, motivation, I employed a grounded theory approach to understand the motivational factors of individuals who work in the middle to higher hierarchy of management in an organizational setting and the lower level employees of the sales department. My research posits that while there still are similar motivational factors between senior managers and employees, several distinctive differences exist. The objective of this study is to identify these differences utilizing various scholarly renowned motivational theories with the grounded theory as the methodological approach. The prime distinguishing features uncovered in this paper are that all senior managers report three main motivating factors at work: employee progression, good relationship with colleagues and satisfaction from influencing company direction. On the other side of the spectrum, all employees who work in sales regard monetary rewards, appreciation and recognition from their bosses, and guidance from their bosses as their ultimate drive. The study also identified a few similar otivational factors, namely ‘seek challenge’ and ‘need for affiliation’ as the force that keeps them passionate at their organizational settings.